2021 6th International Conference on Inventive Computation Technologies (ICICT) 2021
DOI: 10.1109/icict50816.2021.9358506
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Indian State/City Covid-19 Cases Outbreak Forecast utilizing Machine Learning Models

Abstract: S everal scene supposition models for COVID-19 are "be ing utilized by experts around the globe to settle on trained choices and keep up fitting control measures. Man-made awareness Machine Learning (ML) based choosing fragments have shown their significance to foresee perioperative results to improve the dynamic of things to come course of activities. The ML models have been utilized in different application spaces which required the obvious check and prioritization of undesirable parts for a danger. A few su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…If the value of R 2 is deduced to be 1, it denotes that the regression predictions accurately align with the data. Thus, the closer the value of R 2 is to 1, the more influential the model is in predicting trends [19]. The random forest algorithm is a popular unsupervised machine learning algorithm, and it is employed for classification [20,21].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…If the value of R 2 is deduced to be 1, it denotes that the regression predictions accurately align with the data. Thus, the closer the value of R 2 is to 1, the more influential the model is in predicting trends [19]. The random forest algorithm is a popular unsupervised machine learning algorithm, and it is employed for classification [20,21].…”
Section: Methodsmentioning
confidence: 99%
“…Upon obtaining the samples and analyzing the virus genetics, it was established that it caused the outbreak. The virus was named Coronavirus 2019 (COVID- 19) by the WHO in February 2020 [7], while some studies found that this deadly COVID-19 virus is associated with SARS-CoV-2 [8,9]. With its 204 million population, Pakistan saw first of its case in February 2020 [10].…”
Section: Introductionmentioning
confidence: 99%
“…Agarwal et al [1] describe the use of machine learning models to enhance diagnostic accuracy for thyroid diseases, while Chakraborty et al [2] leverage BERTpowered models to detect AI-generated content, highlighting advancements in preserving textual authenticity. Degadwala et al [3] employ machine learning regression techniques to forecast cholera patterns, aiming for precise and actionable disease prediction.…”
Section: Literature Studymentioning
confidence: 99%